Institutionalization of Ukrainian Nationalism: Difference of "Svoboda" ("Liberty") and "Praviy Sektor" ("Right Ssector") Ideology - A. A. Tokarev (MGIMO University Press, 2014)
The article examines the history of the formation of Ukrainian nationalist parties "Svoboda" and "Praviy sektor". First, that they express a structured nationalism and Russophobia in Ukrainian political space. Secondly, in Russia it has become customary to identify one with another. The paper gives an overview of the basic civil identities in Ukraine, Eastern and Western. The author postulates that their conflict lies at the heart of the growing popularity of both nationalist parties. In addition, this process was provoked by the reunion of Crimea and Russia and by the civil war in the south-east of Ukraine. Before the Crimean crisis Ukrainian nationalism had primarily historical roots, and in many respects it was created by attitude of empire elites (the Russian and Soviet Empires) to Ukrainians and their nation-state formations. After March-2014 it began to acquire a geopolitical indication exactly - Russia is perceived as an enemy. Two of the most famous actors of the Ukrainian nationalists and anarchists parties in modern Russia are "Svoboda" and "Praviy sektor". They have fundamentally different origins. "Svoboda" is a systematic force in Ukrainian politics for almost 20 years. Unlike it "Praviy sektor" was established like a party only in December 2013 within a framework of the Euromaidan. Due to the inability to compare the electoral history of both parties the author pays attention to the comparative analysis of their ideologies. Specific manifestations of extremism of "Svoboda" and "Praviy sektor" are not subjects of this research.